PENGARUH STRATEGI PEMASARAN TERHADAP MINAT BELI PELANGGAN PADA PAKET WISATA DI NUANSA TOUR AND TRAVEL BANDUNG (STUDI KASUS PADA NUANSA TOUR AND TRAVEL BANDUNG TAHUN 2023) - Alya Putri Gustira Munaf; Sri Widaningsih (JURNAL LENTERA BISNIS, 2024)
This research aims to identify and analyze the impact of marketing strategies on consumer purchase intention at Nuansa Tour and Travel Bandung. This research uses a descriptive quantitative method with a survey approach, utilizing questionnaires distributed to consumers who have seen Nuansa Tour and Travel content on social media. The variables studied include the marketing mix (product, price, place, promotion, people, process, and physical evidence) and consumer buying interest, which are measured using a Likert scale. The data analysis technique uses a simple linear regression test to determine the relationship between marketing strategies and purchase intention. This research provides insight for Nuansa Tour and Travel in developing more effective marketing strategies to increase consumer buying interest. Recommendations include improving service quality, adjusting competitive prices, optimizing distribution channels, and strengthening promotions through social media. Thus, Nuansa Tour and Travel can better fulfill consumer needs and preferences and increase their competitiveness in the tourism market.